Autistic Adult Health and Professional Perceptions of It: Evidence From the ASDEU Project - Micai, Martina; Ciaramella, Antonio; Salvitti, Tommaso; Fulceri, Francesca; Fatta, Laura Maria; Poustka, Luise; Diehm, Robert; Iskrov, Georgi; Stefanov, Rumen; Guillon, Quentin; Rogé, Bernadette; Staines, Anthony; et al. (Frontiers in Psychiatry, 2021)
The Autism Spectrum Disorders in the European Union (ASDEU) survey investigated the knowledge and health services experiences of users and providers to identify room for improvement in health care for autistic adults. An online survey designed for autistic adults, carers of autistic adults, and professionals in adult services was translated into 11 languages and distributed electronically by organizations and in-country adult services facilities in 2017; 522 autistic adults, 442 carers, and 113 professionals provided answers to the health questions. Professionals, the majority in non-medical services, appeared to be poorly informed about whether certain co-occurring conditions were more frequent in autistic adults than typical adults – especially some medical conditions, suicide attempts, accidents, and pain. A minority of autistic adults reported preventive health behaviors such as routine health check-ups. The majority of users and providers expressed the desire to make health care services more user-friendly for autistic adults. Among the three groups, less than 20% of responders knew an organization or clinician which has developed a way to monitor health, and prevent poor health, that works well for adults on the autism spectrum. Efforts should be focused on 1) professionals’ education on risks for co-occurring conditions in autistic adults; 2) promoting preventive health behaviors; 3) making services user-friendly for autistic adults and their families; 4) encouraging knowledge of good local services.